PERENCANAAN ARSITEKTUR ENTERPRISE MENGGUNAKAN TOGAF ADM VERSI 9 (Studi Kasus: Bimbel Salemba Group) - Nela Rizky; Fitroh Fitroh; Asep Fajar Firmansyah (UIN Syarif Hidayatullah Jakarta, 2017)
Salemba Group Guidance Group (SG) is an institution engaged in the field of education consultants and tutoring. investment of Bimbel SG on SI / TI body has not been effective, this can be seen from the failure of eCors system implementation caused by lack of careful planning of the system, the system development is still adhoc, and not done by experts. This leads to a kuangnya planning on the development of SI / IT, resulting in unconformity between the strategy of SI / IT with its business strategy. In developing SI / IT, a mature architectural plan is required to plan and manage SI / IT, in order to avoid recurrence of failures in system management. Based on existing facts, an enterprise architecture planning for data management, application, and technology was established, with the aim of assisting Bimbel SG in achieving its objectives. In this research, enterprise architecture planning is made using TOGAF (The Open Group Architecture Framework) with ADM (Architecture Develoment Method) method. This enterprise architecture planning will result in blueprint business architecture, application architecture, data architecture, technology architecture, gap analysis on each architecture, and roadmap of application implementation for Bimbel SG.